(untitled) (Iranian Journal of Kidney Diseases, 2010)
Hepatitis C virus (HCV) infection is frequent among kidney transplant recipients, and it is currently the major cause of chronic liver disease following kidney transplantation. The presence of HCV infection has been found to negatively affect the morbidity and mortality rates in patients on dialysis, as well; it seems that kidney transplantation is a reasonable treatment option after a careful pretransplant evaluation. Nevertheless, there are several questions about the indications of kidney transplantation, pretransplant evaluation, transplantation from HCV-infected donors, patient and graft survival rates, and kidney diseases associated with hepatitis C virus after kidney transplantation. This review deals with the most current information on pretransplant and posttransplant evaluations, complications, treatment, and prognosis of HCV-infected kidney transplant recipients.